Systematic Review of the Effects of Oat Intake on Gastrointestinal Health. Issue 10 (6th September 2021) - Valido, Ezra; Stoyanov, Jivko; Bertolo, Alessandro; Hertig-Godeschalk, Anneke; Zeh, Ramona Maria; Flueck, Joelle Leonie; Minder, Beatrice; Stojic, Stevan; Metzger, Brandon; Bussler, Weston; Muka, Taulant; Kern, Hua; et al.
ABSTRACT: Background: Oats are a food source with multiple health benefits that could support beneficial bacterial groups and provide important bioactive compounds for the gut. Objectives: This review explores the association between oat intake, gastrointestinal (GI) symptoms, and microbial community changes in individuals with celiac disease (CeD), irritable bowel syndrome (IBS), and inflammatory bowel disease (IBD) and without GI disease. Methods: Four databases and Google Scholar were systematically searched from inception until April 29, 2021. Clinical trials, observational studies, and in vitro studies with human gut–derived samples were included. Results: There were 84 articles [23 randomized controlled trials (RCTs), 21 nonrandomized trials, 8 observational studies, and 32 in vitro studies] included. Oat intake increased total bacterial count, Lactobacilli spp., and Bifidobacterium spp. in healthy individuals and those with CeD. There was an increased concentration of short-chain fatty acids and improved gut permeability with oat intake but with no significant quality-of-life difference. In some individuals with CeD, consumption of certain oat types was associated with worsening of GI symptoms. We found no studies reporting on IBS and only 3 for IBD. The quality of RCTs showed some concerns mostly in domains of randomization (73.9%), whereas the quality of evidence of non-RCTs, observational studies, and in vitro studies was satisfactory. Conclusions: Oat intake was associated with the increase of beneficial bacterial groups in individuals without GI disease and those with CeD. Most studies showed no changes in GI symptoms with oat consumption. In vitro studies in CeD provide insight to oat-sensitive individuals and their GI mucosa, but the clinical studies remain limited, precluding our ability to draw firm conclusions. The prevalence of oat sensitivity in individuals with CeD should be further explored as this could improve clinical management and facilitate inclusion of oat in the diet for this population.